GIS based Land Information System for Medchal Mandal of R.R. District - Reddy, M. Sunandana; Kumar, L. Harish (International Journal of Computer Sciences and Engineering, 2018)
Modern technologies of remote sensing and GIS like geo-data processing, earth observation data processing and analysis are needs for researchers. This work dedicates to create a land information system over agricultural, rural and urban development areas of Medchal Mandal of Rangareddy Dist. The main task of the work is to set up a land information database in GIS database. The main function of the work is starting with acquisition of existing geodata and information, maintenance, utilization and transferring of data. In this paper, applications of Remote Sensing and GIS for various advance classification techniques together with their accuracy based on performance evaluation, on land use studies are given emphasis. The research conducted on Medchal Mandal, Rangareddy District, Telangana, India. The goal of the research is to develop a land valuation method based on a land information system for selected areas. The establishment of a land information system for mandal will contribute to the National Land Information System. It is very important to analysis and uses the outcomes on a national level and to give knowledge on Geographic Information System to researchers and land managers in the land management sector. The results will promote good governance and offer fact based information to decision makers.